Evaluation of the relationship of posterior tibial slope with gender and age in Turkish population with 3 different methods - Seyhmus Kavak; Sehmuz Kaya (BMC Musculoskeletal Disorders, 2024)
Abstract Background This study aimed to reveal the posterior tibial slope (PTS) angle with 3 different methods in a large case group in the Turkish population. In addition, the reproducibility of the measurement methods used was questioned while determining the age groups, gender and side relationship of this angle. Materials and methods In our retrospective study, radiographs of both knees were evaluated in all 610 patients (344 women, 56.4%) aged 25–65 years. PTS angles were measured by a radiologist and an orthopedist using anterior tibial cortex (ATC), posterior tibial cortex (PTC) and proximal tibial anatomical axis (PTAA) methods. The relationship of these angles with age group and gender, and the intra-class and inter-class correlations of all three methods were evaluated. Results The mean and standard deviation (SD) of PTS angle was 11.03 ± 2.33° with ATC method, 6.25 ± 2.22° with PTC and 8.68 ± 2.16° with PTAA, and the difference was significant (p < .001). In the evaluation according to age groups, the highest mean PTS angles were detected in cases aged 25–35 (9.63 ± 1.97° [mean ± SD] by PTAA method), and there was a significant difference in comparison with other age groups (p < .05). In comparison with age groups, higher mean PTS angles were found in women and on the right side, but the difference was not statistically significant (p > .05). The intraclass and interclass correlation coefficient (ICC) of all three methods was excellent (ICC > 0.91). Conclusion This study emphasizes that the mean PTS angle in Turkish population is higher than the angle values ​​recommended by prosthesis manufacturers, and factors such as patient age and gender should be calculated in order to ensure more effective prostheses to be applied to patients.